NURSES’ KNOWLEDGE AND ATTITUDE TOWARDS PEDIATRICS’ PAIN MANAGEMENT AT SIR GANGA RAM TEACHING HOSPITAL LAHORE - Amna Hanif; Bushra Nausheen; Fazeelat Bibi (International Journal of Contemporary Issues in Social Sciences, 2024)
Effective pediatric pain management remains a critical challenge in healthcare, impacting patient outcomes and quality of life. This cross-sectional study conducted at Sir Ganga Ram Teaching Hospital, Lahore, aimed to assess the knowledge and attitudes of 52 nurses regarding pediatric pain management. Findings revealed that 69.4% of nurses’ demonstrated good knowledge, with notable disparities observed between those working in pediatric wards versus outpatient departments. Attitudes were generally favorable, with 68.2% of nurses prioritizing pain management, particularly those with more than 5 years of experience. However, significant gaps in knowledge and the need for ongoing education highlight opportunities for improving pediatric pain management practices among healthcare providers in similar settings. Future research should incorporate qualitative approaches to better understand the nuances of pediatric pain management attitudes among nurses.